Estrus response and conception rate in non-descript goats synchronized with TRIU C and PGF 2 α - B.Indhumathi; Cecilia Joseph; K. Kulasekar; S. N. Sivaselvam; T. Sarath (Indian Journal of Veterinary and Animal Sciences Research, 2025)
In the present study thirty parous, healthy does were selected from Goat Breeding unit, Post Graduate Research Institute in Animal Sciences, Kattupakkam, Kanchipuram district, Tamil Nadu and randomly divided into three groups of ten each. Group I does were treated with 125 microgram of PGF 2α intramuscularly and Group II does were kept with intravaginal progesterone device TRIU C for seven days and an intramuscular injection of 50 microgram of PGF2α on the sixth day of treatment and ten does served as control. The mean ± SE estrus onset interval in control and treatment groups were 207±55.35, 55 ± 0.50 and 36.40 ± 0.40 hours respectively and significant difference was observed between treatment groups. The mean ± SE duration of estrus and estrus response in the groups were non- significant. The present study concluded that the use of progesterone device (TRIU C and PGF 2α) enhanced the estrus response, shortened the duration for onset of estrus, high estrus intensity score and well pronounced estrus behavior as compared to PGF2α alone treated goats. The conception rate was higher in group II (60 %) as compare to other groups even though it was non-significant. The present study concluded that the progesterone device (TRIU C and PGF2α) treated group has shown better estrus response, higher estrus intensity score and improved conception rate in non-descript goats.